Anne Carson and the deconstruction of literary genre. - Gómez Masdeu, Alejandro (Escritura e Imagen, 2024)
In this article we intend to show the presence of Jacques Derrida in Anne Carson’s poetic work. Derrida is not only mentioned by Carson, which in itself demonstrates her interest in him, but it is also possible to establish notable formal similarities between some of Carson’s and Derrida’s works, as well as a certain closeness between the thought of the French philosopher and the presuppositions of Carson’s poetics, both in the general perspective of Derridean deconstruction and, singularly, in the deconstruction of literary genres, which is characteristic of the Canadian poet’s oeuvre and which Derrida theorizes in a certain way in The Law of Genre. Thus, we believe that Jacques Derrida’s positions can be a privileged framework for understanding this dimension of Carson’s work, which in fact is often considered his most characteristic feature.